fatwa KETENTUAN FATWA TERKAIT PRODUK PENGHIMPUNAN DANA PADA LKS ASPEK HUKUM & ETIKA - muhamad ragiel saputra (Fakultas Ekonomi dan Bisnis Islam Institut Pesantren Sunan Drajat Lamongan, 2025)
This study discusses the fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) regarding fundraising products in Sharia Financial Institutions (LKS), particularly in the form of savings, demand deposits, and term deposits. LKS are financial institutions that operate based on sharia principles derived from the Qur'an and hadith, avoiding the practice of riba (interest) and transactions that contradict Islamic law. This study emphasizes the importance of understanding the fatwas governing these products to ensure that the management of funds adheres to sharia principles. Through a normative and empirical legal approach, this article explores the mechanisms of fundraising in Islamic banking, particularly through Mudharabah and Wadi'ah contracts. The primary aim of this study is to provide guidance for the public in selecting Sharia-compliant fundraising products and to understand the rights and obligations of customers in transactions with LKS. This article also examines the legal and ethical implications of DSN-MUI fatwas regarding savings, demand deposits, and term deposits, as well as the challenges faced in implementing these products in Indonesia.